BIOMASSA DAN KERAPATAN LAMUN BERDASARKAN RASIO N:P PADA SEDIMEN DI PERAIRAN PANTAI TRIKORA KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Febriyantoro, Dodik; Tanjung, Afrizal; Nurrachmi, Irvina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in January – March 2016 in coastal waters of MalangRapat, Bintan Regency, Kepulauan Riau Province. The aims of this study were to determinethe nutrient content of sediment in seagrass ecosystem and to determine the ratio of N:P inthe sediments by different of antropogenic and determine the relationship of nutrient withdensity and biomass of seagrass. The parameters measured were included physical andchemical parameters of marine waters. The density was computed using a quadratic transect,while seagrass biomass was calculated by measuring dry weight of shoot. The value ratio ofN:P in the sediment was total of nitrogen by Kjehdahl method and phosphorus total withDouble Acid method. The results showed the average nitrogen content was 0.003621–0.003966% and the average phosphorus was 0.000036–0.000090%. The density of seagrassin the coastal of Trikora Beach Malang Rapat was 54.78–56.33 shoots/m2 and biomass ofseagrass was 261.37–275.65 g/m2. Station II had a ratio of N:P = 44:1 and provided goodleverage, this can be indicated also by the total biomass and density of seagrass at this stationwas the highest. The Nitrogen and Phosphorus in the sediment with density and biomass ofseagrass had a very weak relationship, there are other factors that might affect the density andbiomass of seagrass in which were not measured in this study.Keywords: Seagrass Ecosystem, Density, Biomass, Rasio N:P, Sediment, Trikora Beach